2010
DOI: 10.1002/hed.21322
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of functional decline in locally advanced head and neck cancer patients from South Brazil

Abstract: The physical and psychological impact of HNSCC and its treatment are universally experienced; yet, screening and intervention for symptoms such as fatigue and stress are not typical clinical practice. Moreover, assessment of functional status is usually limited to chewing and swallowing. This study identified symptoms that require systematic intervention and randomized trials with functional independence as the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
3
13
0
1
Order By: Relevance
“…29 In the present study, a high prevalence of white skin individuals (90.04%) was observed, similar to the findings from a study conducted recently in the southern states of Brazil 30 and the Midwest of the United States. 31 However, Hayat et al 32 observed a higher prevalence of head and neck cancer among AfricanAmerican descendants from different areas of the United States.…”
supporting
confidence: 92%
“…29 In the present study, a high prevalence of white skin individuals (90.04%) was observed, similar to the findings from a study conducted recently in the southern states of Brazil 30 and the Midwest of the United States. 31 However, Hayat et al 32 observed a higher prevalence of head and neck cancer among AfricanAmerican descendants from different areas of the United States.…”
supporting
confidence: 92%
“…In a large cohort of older people, Ahacic et al have demonstrated that fatigue was independently related to activity limitations . Furthermore, fatigue has a negative impact on daily living activities also in the setting of chronic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Horiot reported that older patients may suffer from a more important functional impact, and may therefore be more vulnerable to the secondary effects of the treatment (Horiot 2007). The need for assistance with IADLs and ADLs respectively doubled and quadrupled in a vulnerable elderly H&N cancer population 6 months after treatment start, with fatigue as a predictive factor for IADL deterioration (Silver et al 2010). Likewise, in our study, self-reported fatigue was found to be significantly more present in vulnerable patients at both time points, and significantly worsened in both groups.…”
Section: Discussionmentioning
confidence: 99%